Analisis Perbandingan Tingkat Kesehatan Bank Menggunakan Pendekatan Risk Profile, Good Corporate Governance, Earning, Capital (RGEC) Pada Bank Central Asia Dan Bank Mandiri Periode 2018-2022 - Eka Indah Apriliani; Adiati Trihastuti (Jurnal Kajian dan Penalaran Ilmu Manajemen, 2023)
This study aims to determine the comparison of the soundness level of PT. Bank Central Asia Tbk and PT Bank Mandiri (Persero) Tbk based on Bank Indonesia Regulation (PBI) No.13/1/PBI/2011 concerning Assessment of Commercial Bank Validity Level using RGEC method (Risk Profile, Good Corporate Governance, Eaming and Capital). The period used in his research was 5 years, starting from 2018 to 2022. The type of research used is descriptive research kualitative. The data obtained is in the form of secondary data in the form of annual financial statements of PT. Bank Central Asia Tbk and PT Bank Mandiri (Persero) Tbk. This study used an assessment method based on the calculation of each variable. Risk Profile assessment uses Non Performing Loan (NPL) and Loan to Deposit Ratio (LDR) ratios. Good Corporate Governance uses the results of Self Assessment of GCG implementation that has been published by PT. Bank Central Asia Tbk and PT Bank Mandiri (Persero) Tbk. Earnings valuation uses the ratio of Return On Asset (ROA) and Operating Expense Against Operating Income (BOPO).. Capital uses the Capital Adequacy Ratio (CAR). The results of research and data analysis using RGEC (Risk Profile, Good Corporate Governance, Earning and Capital) methods can be concluded that PT. Bank Central Asia Tbk and PT Bank Mandiri (Persero) Tbk received a Composite Rating of 1 (PK-1) with the predicate "Very Healthy". This is evidenced by PT Bank Central Asia Tbk obtaining an average composite value of 97.33% and PT Bank Mandiri (Persero) Tbk of 94.00% for the past 5 years. So it is proven that PT Bank Central Asia has a higher performance than PT Bank Mandiri (Persero) Tbk.